Corrective Osteotomy for Symptomatic Radial Head and Neck Malunions in the Skeletally Immature. Issue 3 (3rd March 2023) - Bhashyam, Abhiram R.; Hadley, Scott R.; Beatty, Evan W.; Waters, Peter M.; Bae, Donald S.
Abstract : Background: Radial head and neck fracture malunion can lead to pain, stiffness, deformity, and functional limitations. This study analyzed the early radiographic and functional outcomes of corrective osteotomy for symptomatic radial head and/or neck malunion in skeletally immature patients. Methods: Thirteen pediatric patients treated with corrective osteotomy for symptomatic radial head and/or neck malunion from 2004 to 2018 were identified. Radiographic union, range of motion, pain, and complications were recorded. Functional outcomes were assessed using the Broberg and Morrey Elbow Scale. Results: The average age at the time of surgery was 12.3 years (range: 8.6 to 16.3). The mean time from injury to osteotomy was 7.5 months (range: 2 to 24.1 mo). Before osteotomy, mean radial head-shaft angulation was 23 degrees (range: 5 to 57 degrees), mean displacement was 76% (range: 0 to 55), average elbow flexion contracture was 18 degrees (range: 0 to 60 degrees), and average elbow flexion was 112 degrees (range: 95 to 135 degrees). After a mean follow-up of 14.3 months, 12 of 13 osteotomies (92%) healed; 1 patient had a painless nonunion. The number of patients reporting pain decreased from 9 to 2 ( P =0.012). Radiographic alignment and range of motion improved in all patients. Mean angulation and displacement improved to 8 degrees (range: 2 to 15 degrees, P =0.001) and 3% (range: 0 to 18 degrees, P =0.001), respectively. Mean elbow flexion contracture was reduced to 5 degrees (range: 0 to 30 degrees, P =0.008), and the average elbow flexion increased to 128 degrees (range: 100 to 135 degrees, P <0.001). Three patients underwent implant removal for complications, including heterotopic ossification and avascular necrosis. Physeal arrest did not lead to any adverse sequelae. The sole case of avascular necrosis had a reduced range of motion but no pain. The mean postoperative Broberg and Morrey score was 91.1; 7 patients had excellent postoperative scores, 4 good, and 2 fair. Conclusions: Corrective osteotomy for symptomatic malunion of the radial head and/or neck in skeletally immature patients can improve elbow alignment, motion, pain, and function. Preservation of the soft-tissue attachments to the proximal epiphysis and rigid internal fixation are critical components of this surgical technique. Level of Evidence: Therapeutic Level IV.